Duration of untreated illness in first-treatment bipolar I disorder in relation to clinical outcome and cannabis use. (30th December 2016) - Kvitland, Levi Røstad; Ringen, Petter Andreas; Aminoff, Sofie Ragnhild; Demmo, Christine; Hellvin, Tone; Lagerberg, Trine Vik; Andreassen, Ole Andreas; Melle, Ingrid
Abstract: There is little knowledge about the role of the duration of untreated bipolar (DUB) illness in first-treatment bipolar disorder I (BD I), its association with symptoms at start of first treatment, and development over the first year, and limited knowledge about factors that influence the length of DUB. Substance use has shown to delay identification of primary psychiatric disorders, and while cannabis use is common in BD the role of cannabis in relationship to DUB is unclear. The aim of the present study is to examine the associations between DUB and key clinical outcomes at baseline in BD I, and at one year follow-up, and to evaluate the influence of cannabis use. Patients with first-treatment BD I (N=62) completed comprehensive clinical evaluations, which included both DUB and the number of previous episodes. There were no significant associations between DUB and key clinical outcomes. Longer duration from first manic episode to treatment was associated with risk of starting excessive cannabis use after onset of the bipolar disorder. The main finding is the lack of significant associations between features of previous illness episodes and clinical outcomes. Long duration of untreated mania seems to increase the risk for later cannabis use. Highlights: Investigating duration of untreated illness (DUB) in first treatment Bipolar I. No associations between DUB and key clinical outcomes. Number of previous depressive episodes might be a better illness marker. Long manic DUB associated with increased risk of later cannabis use. If replicated this may affect future research, diagnostics and clinical practice.